Why does business involve in corporate responsibility? - Abdul Hamid, Fathilatul Zakimi; Atan, Ruhaya (2011)
The study shows that how coercive isomorphism has influenced business to associated its Corporate Responsibility initiatives into business core activity.By employ case study methodology, the research demonstrates that the well defined CR framework, is not only improved business financial performance, but also has changed employee behaviors that lead into business sustainability.Furthermore, our result supports prior literature on top management strategic leadership is essential in successful CR planning and implementation.